Structure of dimeric axonemal dynein in cilia suggests an alternative mechanism of force generation. Issue 7 (2nd July 2014) - Ueno, Hironori; Bui, Khanh Huy; Ishikawa, Takuji; Imai, Yohsuke; Yamaguchi, Takami; Ishikawa, Takashi
<x xml:space="preserve">Abstract</x> The mechanism by which the two different heads of the ciliary outer dynein arm produce force to translocate the microtubule during beating is still unknown. In this report we use cryo‐electron tomography and image processing to analyze the conformational changes and the relative abundance of each conformation of the two dynein heads from mouse respiratory cilia. In the absence of nucleotides the majority of dynein dimers are in the apo form and both heads are tightly packed, whereas they are dissociated and move independently in the presence of nucleotides. The head of the external outer arm dynein heavy chain has a diagonal shift toward both the neighboring B‐tubule and the proximal end of the axoneme, while the head of the internal heavy chain shifts only longitudinally toward the proximal end. In the presence of nucleotides a significant number of the dynein dimers have two heads overlapped in the proximal shifting form or overlapped in the apo form. During ciliary bending axonemal dynein translocates microtubules by moving with short steps and two heads stay at the same position longer than cytoplasmic dynein. This demonstrates that the step of the outer arm dynein dimer is not dominated by the hand‐over‐hand motion, but also indicates the difference between axonemal dynein and cytoplasmic dynein. © 2014 Wiley Periodicals, Inc.